1994
DOI: 10.3354/meps113095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolved mercury on embryo-genesis, survival, growth and metamorphosis of Crassostrea gigas oyster larvae

Abstract: The effects of mercury (Hg) concentrations ranging from 0 (control) to 1024 pg 1-' upon embryogenesis, survival, growth and metamorphosis of Crassostrea gigas (Thunberg) oyster larvae were investigated. Embryogenesis was abnormal in 50 % of the individuals at 11 pg I-' The 48 h LDS" for D-shaped, urnbonate and pediveliger larvae were 33, 115 and 200 pg 1-' respectively. The increase in was partially explained by the larval weight increase, although weight-specific tolerance to Hg was higher in smaller larvae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 39 publications
(56 reference statements)
5
39
2
Order By: Relevance
“…Other morphological abnormalities include convex hinge and protrusion of the mantle, both of which are typical criteria used to distinguish between normal and abnormal development of veliger larvae in embryotoxicology bioassay (His et al 1997). Although no observations were made on larval behaviour in the present study, Beiras & His (1994) reported swimming inhibition in larvae with protruded mantle, which could reduce environmental fitness.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Other morphological abnormalities include convex hinge and protrusion of the mantle, both of which are typical criteria used to distinguish between normal and abnormal development of veliger larvae in embryotoxicology bioassay (His et al 1997). Although no observations were made on larval behaviour in the present study, Beiras & His (1994) reported swimming inhibition in larvae with protruded mantle, which could reduce environmental fitness.…”
Section: Discussionmentioning
confidence: 59%
“…Most previous studies on the effect of ocean acidification have dealt with adult individuals; little is known about CO 2 impacts on marine organisms during early development. In addition, several toxicity studies rank bivalve life stages in terms of relative sensitivity to sublethal and lethal effects as: embryos > veligers (D-larvae) > metamorphosing larvae > pediveligers > adults (Beiras & His 1994, His et al 1999. Shell synthesis is significantly suppressed when larvae of the oyster Crassostrea gigas are exposed to seawater equilibrated with CO 2 -enriched (2000 ppm) air (pH 7.4; Kurihara et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…During later larval development CaCO 3 deposition is converted to aragonite and following settlement and metamorphosis, calcite, the most stable CaCO 3 polymorph, is deposited [72,73]. Rather than earlier stages being more sensitive than later [37] there is an absence of evidence of hierarchical sensitivity and more evidence of sensitivity of larval stages being species specific. The pediveligers of S. glomerata were more sensitive than spat to changes to CO 2 and temperature, but this reversed in C. gigas with newly metamorphosed spat showing greater sensitivity than pediveligers [39].…”
Section: Molluscsmentioning
confidence: 99%
“…Not only has it been suggested that the impact of ocean acidification will be more significant for larvae than adults [14], but it will be most significant for the earlier sensitive life history stages; including egg and sperm production, fertilisation, cleavage, than the later life history stages of larval development and dispersal, settlement and post-settlement survival, especially for molluscs and echinoderms [7,14,[33][34][35][36] (Figure 1). Indeed it has been suggested that the sensitivity of larvae is hierarchical, being most sensitive when embryos and least sensitive as pediveligers and metamorphs, following a linear sequence; embryos>veligers (D larvae)> pediveligers>metamorphs>adults [37]. Such sensitivity may vary among marine groups.…”
Section: Introductionmentioning
confidence: 99%
“…High toxicity and bioaccumulation give Hg a well-known ecotoxicological relevance among the heavy metals (reviewed by Cossa et al 1990). Crassostrea gigas (Thunberg) embryogenesis was found to be abnormal in 50 % of the individuals at 11 pg Hg I-', and larval growth significantly retarded at 4 pg 1-' (Beiras & His 1994).…”
Section: Introductionmentioning
confidence: 99%